Use of a perforator-based flap from the ulnar palmar artery for the repair of defects caused by the treatment of severe contractures due to Dupuytren's disease - Jiangping Dai; Jiangping Dai; Hui Wang; Haifeng Wang; Haifeng Wang; Xinyang Sun; Xinyang Sun; Yihan Zhang; Yihan Zhang (Frontiers in Surgery)
ObjectiveThe aim of this study was to investigate the clinical effectiveness of a perforator flap from the ulnar palm in repairing soft tissue defects in the palm and fifth digit following severe Dupuytren's contracture.MethodsA retrospective study was conducted between March 2013 and January 2023. In total, 25 patients with soft tissue defects that occurred after severe Dupuytren's contracture release were treated using a perforator flap from the ulnar palm. Improvements in symptoms and functionality were assessed and compared before and after surgery. Data regarding the degree of contracture, two-point discrimination, and the total active motion (TAM) scale of the affected hand were collected by the same physician at the specified time points (preoperative, postoperative, and final follow-up), along with an evaluation of the donor and recipient areas of the flap. Concurrently, patients completed the visual analog scale (VAS) and disability of arm, shoulder, and hand (DASH) questionnaires.ResultsAll 25 flaps survived uneventfully, and the wound healed primarily. The follow-up time was 15–26 months (average, 20.48 months). At the final follow-up, the patient satisfaction score related to flap appearance ranged from 4 to 5 (mean, 4.72). The average two-point discrimination value of the flap was 5.52 ± 0.97 mm. The contracture of the affected hand was improved with a mean TAM of 229° ± 16.75°. Furthermore, the degree of pain and functional status of the affected hand had improved (P < 0.05).ConclusionA perforator flap from the ulnar palm is a good option to repair the wound that occurs after severe Dupuytren's contracture release.